The Association Between Social Support, COVID-19 Exposure, and Medical Students' Mental Health - Yin, Yi; Yang, Xingjie; Gao, Lan; Zhang, Suoyuan; Qi, Meng; Zhang, Ligang; Tan, Yunlong; Chen, Jingxu (Frontiers in Psychiatry, 2021)
Background The coronavirus disease- 2019 (COVID-19) pandemic has halted in-person medical education worldwide. Limited studies have reported the mental health status of medical students during this public health emergency. This study aimed to explore the association of personal virus exposure, regional epidemic condition, and social support with medical students’ depressive and anxiety symptoms during the COVID-19 outbreak in China. Methods In February 2020, 5,982 medical students (Mean age = 21.7, Median age = 22 years old; 60.0% females) completed an online survey consisting of demographics, personal virus exposure, the Patient Health Questionnaire, the Generalized Anxiety Disorder Scale, and the Social Support Rating Scale. Results The prevalence rates of mild to severe depressive symptoms and anxiety symptoms were 35.2% and 22.8%, respectively. Multivariate linear regression showed that students with low- or medium-level social support had a higher risk of experiencing depressive or anxiety symptoms than those with high-level social support. COVID-19 exposure was positively associated with mild to severe depressive or anxiety symptoms. Respondents living in provinces with 500 to 1000 confirmed COVID-19 cases had an increased risk of experiencing mild to severe depressive symptoms compared with those living in provinces with less than 100 cases. Other related factors were gender and years of training. Conclusions Some medical students suffered from a poor psychological status during the COVID-19 outbreak. Low social support was a stronger factor related to poor mental status compared with COVID-19 exposure or the provincial epidemic condition. Thus, we suggest colleges or universities provide social support and mental health screening.